Prognostic factors and benefits of adjuvant therapy after pancreatoduodenectomy for ampullary adenocarcinoma: Mayo Clinic experience. Issue 5 (May 2018) - Jin, Zhaohui; Hartgers, Mindy L.; Sanhueza, Cristobal T.; Shubert, Christopher R.; Alberts, Steven R.; Truty, Mark J.; Muppa, Prasuna; Nagorney, David M.; Smyrk, Thomas C.; Hassan, Mohamed; Mahipal, Amit
Abstract: Introduction: Ampullary adenocarcinoma is a rare entity with limited data on prognostic factors. The aim of this study is to identify prognostic factors and assess the benefit of adjuvant therapy in patients with ampullary adenocarcinoma who underwent pancreatoduodenectomy. Methods: A cohort of 121 consecutive patients underwent pancreatoduodenectomy for ampullary adenocarcinoma from 2006 to 2016 at Mayo Clinic in Rochester, MN. All patients were confirmed by independent pathologic review to have ampullary carcinoma. Patient survival and its correlation with patient and tumor variables were evaluated by univariate and multivariate analysis. Results: Fifty three patients (45%) received adjuvant therapy (34 patients had chemotherapy alone, while 19 patients received both chemotherapy and radiation therapy). Fifty seven percent of the patients were diagnosed with advanced stage disease (Stage IIB or higher). Nearly all patients (98.3%) had negative surgical margins. Median overall survival (OS) was 91.8 months (95% CI:52.6 months-not reached). In multivariate analysis, excellent performance status (ECOG: 0), adjuvant therapy, and advanced stage remained statistically significant. Adjuvant therapy was independently associated with improved disease free survival (Hazard ratio [HR]:0.52, P  = 0.04) and overall survival (HR:0.45, P  = 0.03) in patients with advanced disease. Conclusions: Adjuvant therapy was associated with improved survival in patients with resected ampullary cancer, especially with advanced stage disease. A multi-institutional randomized trial is needed to further assess the role of adjuvant therapy in ampullary adenocarcinoma.